The Prison Radicalization Strategies of Feto Prisoners: A Comparison Between Türkiye And Europe (Third Sector Social Economic Review, 2025)
This study comparatively analyzes the radicalization strategies of Fetullah Terrorist Organization (FETO) inmates in Turkey and Europe. Prisons are approached not only as punitive environments but also as spaces where ideological identities and organizational loyalties are reproduced. The analysis is guided by Moghaddam’s Staircase to Terrorism model and Kruglanski’s Significance Quest Theory. Findings show that in Europe, the limited number of FETO inmates restricts collective organizational restructuring; however, individual radicalization persists through political-prisoner identity and victimhood narratives. In Turkey, the post–July 15 shift toward F-type prisons, strict communication controls, psychosocial services, and spiritual guidance programs has significantly impeded organizational continuity. The study concludes that prison radicalization is a multidimensional phenomenon and highlights the need for stronger rehabilitation programs and enhanced international cooperation to support policymaking in this field.
Keywords: FETO; Radicalization; Prisons; Turkiye; Europe